Transactions on Computational Science XVIII Special Issue on Cyberworlds - Gavrilova, Marina L.; Tan, C. J. Kenneth.; Kuijper, Arjan. (Lecture Notes in Computer Science, 2013)
The 18th issue of the Transactions on Computational Science journal, edited by Arjan Kuijper, is devoted to the topic of cyberworlds. The 14 papers in the volume constitute revised and extended versions of a selection of contributions presented at CW 2012, the International Conference on Cyberworlds, held in Darmstadt, Germany in September 2012. The selected papers span the areas of human path prediction, gesture-based interaction, rendering, valence-levels recognition, virtual collaborative spaces, virtual environment, emotional attention, virtual palpation, sketch-book design, animation, and avatar-face recognition.